2017
DOI: 10.1016/j.gexplo.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Petrogeochemical assessment of rock units and identification of alteration/mineralization indicators using portable X-ray fluorescence measurements: Applications to the Fire Tower Zone (W-Mo-Bi) and the North Zone (Sn-Zn-In), Mount Pleasant deposit, New Brunswick, Canada

Abstract: The Mount Pleasant polymetallic deposits are located along the southwestern margin of the Late Devonian Mount Pleasant Caldera Complex in southwestern New Brunswick, Canada. The Fire Tower Zone (W-Mo-Bi) and the North Zone (Sn-Zn-In) comprise the main mineralized zones within the Mount Pleasant deposit. The rock units examined at surface in both zones are highly altered and are surface weathered to some extent. In order to classify these rock units with confidence, the Olympus X-5000 portable X-ray Fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Clever combinations of elements allowed Brand and Brand (2016) to use pXRF for Li exploration, despite this light element being out of reach of pXRF. A similar approach was used by Zhang et al (2017) at the Mount Pleasant deposit (Fire Tower Zone, W-Mo-Bi, and North Zone, Sn-Zn-In). They deduced mineralisation signatures (As and Mo, along with K, Rb, Fe, and Mn depletion, interpreted as the W-Mo mineralisation; and Sn, Zn, Cu, and S with slightly depleted Sr and Ba, representing Sn-Zn mineralisation) from principal component analysis (PCA) of the multi-element pXRF data.…”
Section: Pxrf In Mining and Mineral Exploration Projectsmentioning
confidence: 99%
“…Clever combinations of elements allowed Brand and Brand (2016) to use pXRF for Li exploration, despite this light element being out of reach of pXRF. A similar approach was used by Zhang et al (2017) at the Mount Pleasant deposit (Fire Tower Zone, W-Mo-Bi, and North Zone, Sn-Zn-In). They deduced mineralisation signatures (As and Mo, along with K, Rb, Fe, and Mn depletion, interpreted as the W-Mo mineralisation; and Sn, Zn, Cu, and S with slightly depleted Sr and Ba, representing Sn-Zn mineralisation) from principal component analysis (PCA) of the multi-element pXRF data.…”
Section: Pxrf In Mining and Mineral Exploration Projectsmentioning
confidence: 99%
“…To simplify the collected pXRF dataset, the authors used a chemometrics technique called Principal Component Analysis (PCA). The authors found that an enrichment in Mo and As, and depletion of Fe, Mn, K and Rb indicating mineralization of W and Mo in Mount Pleasant area [23].…”
Section: Pxrf Applied To Mineralogical and Environmental Samplesmentioning
confidence: 97%
“…Wei Zhang [23] and coworkers used pXRF to obtain the geochemical composition, identify lithologic discriminants, and find alteration/mineralization indicators in rocks located in Mount Pleasant polymetallic deposits in southwestern New Brunswick, Canada. Two main regions inside Mount Pleasant Complex were analyzed: The Fire Tower Zone and the North Zone.…”
Section: Pxrf Applied To Mineralogical and Environmental Samplesmentioning
confidence: 99%
“…When purchasing and commissioning a new pXRF analyzer, producing quantitative data is not a "point-and-shoot" exercise. First, there must be a QA/QC program that includes blanks and reference materials (e.g., Fisher et al, 2014;Le Vaillant et al, 2014;Zhang et al, 2017;Lemière, 2018). Then, before quantitative analyses can be made, the user must determine the optimal measurement time and number of spots per sample, and establish a matrix-matched secondary calibration (Hall et al, 2013(Hall et al, , 2014Le Vaillant et al, 2014;Ross et al, 2014aRoss et al, , 2014bBourke and Ross, 2016;McNulty et al, 2018;Martin and Carr, 2020;Adams et al, 2021).…”
Section: Introductionmentioning
confidence: 99%